Evolutionary relationship of three mitten crabs (Eriocheir sp) revealed by mitogenome and 5S ribosomal DNA analysis - Xiaowen Chen; Jun Wang; Lei Huang; Wucheng Yue; Jixing Zou; Chunhong Yuan; Guoqing Lu; Chenghui Wang (Aquaculture and Fisheries, 2017)
To reveal the evolutionary relationship of three mitten crabs (Eriocheir sinensis, E. hepuensis, and E. japonica), complete mitogenomes and nuclear 5S rDNA sequences were analyzed. Sequencing revealed that the mitogenomes analyzed shared conserved organization of the coding and non-coding regions but genetic variation was identified. Among the three mitten crabs distinct tandem repeats were identified in the mitochondrial D-loop region. The 5S gene (5S rDNA) sequence was highly conserved across the three species, whereas non-transcribed spacer (NTS) region exhibit high levels of variation including insertions, deletions and point mutations. Cluster analysis suggested that the three mitten crabs had their own independent 5S rDNA sequence variation and evolutionary pattern. Both mitogenome and 5S rDNA sequence analysis revealed significant genetic variation across the mitten crabs species. Phylogenetic analysis using mitogenome and 5S rDNA sequences demonstrated that E. japonica was relatively more distant from E. sinensis and E. hepuensis. This study extended our previous knowledge and confirmed that the three mitten crabs are likely to be genetically differentiated species. In addition, our study also provided insights into the conservation of pure natural resources of E. sinensis, an important aquaculture species.